Why do citizens not prefer to use e-scooters? Views of the public in the Netherlands - DİRSEHAN, TAŞKIN (My University, 2024)
E-scooters, a burgeoning form of micromobility, are revolutionizing urban transportation systems globally, particularly in the post-pandemic world. The surge in e-scooter adoption introduces novel regulatory challenges for local authorities. Numerous recent studies cater to these policy needs by exploring e-scooter use. However, scant attention has been paid to non-users’ perspectives, which is crucial to understand comprehensively the effect of e-scooters on urban environments. Issues such as accidents, parking problems, and others, which concern city-dwellers, require close attention. To address this research gap, we used a Q-methodology study to examine the diverse views among residents of the Netherlands. Twenty-one respondents ranked 34 statements pertaining to their disincentives to e-scooter use and elucidated their rankings in a follow-up survey. The study unearthed three distinct viewpoints: (1) \"environmentalists\" deem e-scooters as environmentally unfriendly, (2) \"materialist\" exhibit a preference for personal vehicle ownership over shared transport, and (3) \"socializers\" perceive e-scooters as unsuitable for larger groups. These findings set the stage for potential research directions and underline the importance of incorporating diverse public perceptions in micromobility policymaking.
Keywords: Sosyal ve Beşeri Bilimler; Coğrafya; Mühendislik ve Teknoloji; Social Sciences and Humanities; Geography; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Yerbilimleri; ULAŞIM; COĞRAFYA; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; GEOSCIENCES; TRANSPORTATION; GEOGRAPHY; Coğrafya, Planlama ve Geliştirme; Sosyal Bilimler ve Beşeri Bilimler; Toplu taşıma; Geography, Planning and Development; Social Sciences & Humanities; Transportation; E-scooters; Micromobility; Q-methodology; The Netherlands; Urban Environment